Physiological and molecular profiling unveils oat (Avena sativa L.) defense mechanisms against powdery mildew - Ma, Aijie; Liu, Tao; Tian, Wenhui; Chen, Hong; Wang, Guoqing; Zhang, Bo (Frontiers in Plant Science, 2025)
Oat powdery mildew, caused by Blumeria graminis f. sp. avenae (Bga), poses a serious threat to oat production, yet the underlying resistance mechanisms remain largely unclear. In this study, we investigated early-stage defense responses in resistant (BY642) and susceptible (BY119) oat varieties following Bga inoculation using cytological observations, physiological and hormonal measurements, and transcriptomic analysis. Microscopy revealed that Bga penetrates oat tissues directly through epidermal cells rather than stomata. BY642 exhibited a rapid and robust defense characterized by reactive oxygen species (ROS) accumulation and hypersensitive response, tightly regulated by an efficient antioxidant system to prevent cellular damage. Hormone profiling indicated a salicylic acid (SA)-dominated signaling pathway in BY642, accompanied by suppression of jasmonic acid (JA) responses. Transcriptome profiling showed early activation of photosynthesis-related pathways, metabolic reprogramming, and immune-related networks, including MAPK cascades and WRKY transcription factors. Hub genes such as AsGSTU6 and AsWRKY50 were identified as key contributors to resistance. These findings suggest that BY642 employs a coordinated defense strategy integrating ROS dynamics, SA signaling, and transcriptional regulation, providing novel insights into the molecular basis of powdery mildew resistance and potential targets for oat breeding.